Home town news : William Allen White and the Emporia gazette - Griffith, Sally Foreman (OUP E-Books., 1989)
This biography of William Allen White, one of the best known newspaper editors of early 20th century America, is concerned not only with White's career, but also with small-town values and achievements in turn-of-the-century America, when the nation was changing dramatically.